Cancel Culture : Case Study of Sexual Harassment on Followers Autobase Twitter @Areajulid - Yayang Eka Januarda Nisa; Yuhastina .; Nurhadi Nurhadi (Journal Civics and Social Studies, 2022)
Virtual open spaces such as Twitter offer a place for netizens to gather and discuss certain topics. Netizens will issue their own opinions and often end up boycotting/punishing someone who is considered to have made a mistake, which is called cancel culture, experts have different opinions about cancel culture. This study attempts to provide an overview from the field regarding the phenomenon of cancel culture in cases of sexual violence as part of a social control. This study uses a phenomenological qualitative method, the data is taken from the results of interviews and observations to 7 followers of the @AREAJULID autobase account. The results of the study concluded that 1) The informants canceled the perpetrators of sexual violence in different ways. 2) Cancel culture is a means of social control through rumors and gossip.